The planetary scientist's companion - Lodders, Katharina (Oxford University Press, 1998)
A comprehensive and practical book of facts and data about the Sun, planets, asteroids, comets, meteorites, the Kuiper belt and Centaur objects in our solar system. Also covered are properties of nearby stars, the interstellar medium, and extra-solar planetary systems.